2018
DOI: 10.3389/fphys.2018.00862
|View full text |Cite
|
Sign up to set email alerts
|

Acidosis and Phosphate Directly Reduce Myosin’s Force-Generating Capacity Through Distinct Molecular Mechanisms

Abstract: Elevated levels of the metabolic by-products, including acidosis (i.e., high [H+]) and phosphate (Pi) are putative agents of muscle fatigue; however, the mechanism through which they affect myosin’s function remain unclear. To elucidate these mechanisms, we directly examined the effect of acidosis (pH 6.5 vs. 7.4), alone and in combination with elevated levels of Pi on the force-generating capacity of a mini-ensemble of myosin using a laser trap assay. Acidosis decreased myosin’s average force-generating capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…; Jarvis et al . ; Woodward & Debold, ) that used a fatigue‐mimicking environment of pH 6.2–6.5 and ∼20–30 m m P i are similar to the metabolic environment that can be achieved volitionally in vivo . Interpreted together, the greater accumulation of H + and P i in old compared to young adults (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…; Jarvis et al . ; Woodward & Debold, ) that used a fatigue‐mimicking environment of pH 6.2–6.5 and ∼20–30 m m P i are similar to the metabolic environment that can be achieved volitionally in vivo . Interpreted together, the greater accumulation of H + and P i in old compared to young adults (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a strong connection between pH regulation and work capacity has been shown, suggesting that acidosis strongly contributes to fatigue [54]. More specifically, acidosis may impair function of contractile properties by reducing: (a) sarcoplasmic Ca 2+ release and re-uptake, (b) myofibrillar Ca 2+ sensitivity [55] and (c) activity of ATPase [56] and key enzymes of glycolysis such as phosphofructokinase and phosphorylase [57] (Figure 1). However, skinned fiber experiments in variable pH and temperatures have indicated that acidosis, while still important, is not the only reason behind the slowing of contractile velocity observed during fatigue (e.g., [10]).…”
Section: Lactate As a Fatigue Agent And As A Signaling Moleculementioning
confidence: 99%
“…A simplified scheme of the purported effects of acidosis and reactive oxygen species (ROS) based on muscle fatigue literature reviewed in this article. Acidosis has been shown to cause impaired Ca 2+ handling [55] and inhibition of key metabolic enzyme activities [57] as well as to inhibit myosin ATPase [56] affecting force and velocity of contraction [10]. ROS have been shown to cause: impaired sarcolemma ability to depolarize [87], disturbance in calcium release from the sarcoplasmic reticulum and decreased calcium sensitivity of the myofilaments [89], impaired acto-myosin interaction [91], enzyme inhibition [92] and blood flow restriction [93].…”
Section: Figurementioning
confidence: 99%
“…Increasing blood alkalosis alters the pH gradient between the intracellular and extracellular compartments, subsequently leading to the upregulation of the lactate–hydrogen ion (H + ) co-transporter to efflux acidic H + from the active musculature and into circulation [4,5]. During exercise, accelerating the removal of H + is purported to offset fatigue since intracellular acidosis is associated with debilitating effects on the capacity to sustain muscle force production [610]. More specifically, cellular acidosis is suggested to reduce muscle shortening velocity and cross-bridge cycling by inhibiting calcium ion (Ca 2+ ) sensitivity [6,9] and myosin ATPase activity [10,11], whereas additional impairments of key glycolytic enzymes [12,13] and the strong ion difference (SID) [7,14,15] could reduce the available ATP substrates and action potentials necessary to maintain muscular contractions, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…During exercise, accelerating the removal of H + is purported to offset fatigue since intracellular acidosis is associated with debilitating effects on the capacity to sustain muscle force production [610]. More specifically, cellular acidosis is suggested to reduce muscle shortening velocity and cross-bridge cycling by inhibiting calcium ion (Ca 2+ ) sensitivity [6,9] and myosin ATPase activity [10,11], whereas additional impairments of key glycolytic enzymes [12,13] and the strong ion difference (SID) [7,14,15] could reduce the available ATP substrates and action potentials necessary to maintain muscular contractions, respectively. Due to the complexity of fatigue, the role of acidosis in each of these mechanisms is contested as a causative factor [1618].…”
Section: Introductionmentioning
confidence: 99%